Private Retirement Savings in Germany: The Structure of Tax Incentives and Annuitization - Hans Fehr; Christian Habermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The present paper studies the growth, welfare and efficiency consequences of the recent introduction of tax-favored retirement accounts in Germany in a general equilibrium overlapping generations model with idiosyncratic lifespan and labor income uncertainty. We focus on the implicit differential taxation of specific savings motives, the mandatory annuitization of benefits and the impact of special provisions for low-income households. The simulations indicate that the reform improves overall economic efficiency by about 0.6 percent of aggregate resources, but welfare decreases significantly for future generations. Finally, we show that special provisions could be very effective in raising the participation of low-income households despite their low budgetary cost.
Keywords: H55; J26; 330; Individual retirement accounts; annuities; stochastic general equilibrium